Profiling of circular RNA N6‐methyladenosine in moso bamboo (Phyllostachys edulis) using nanopore‐based direct RNA sequencing. Issue 12 (31st August 2020) - Wang, Yongsheng; Wang, Huihui; Xi, Feihu; Wang, Huiyuan; Han, Ximei; Wei, Wentao; Zhang, Hangxiao; Zhang, Qianyue; Zheng, Yushan; Zhu, Qiang; Kohnen, Markus V.; Reddy, Anireddy S. N.; et al.
Abstract: N 6 ‐methyladenosine (m 6 A) is a prevalent modification in messenger RNAs and circular RNAs that play important roles in regulating various aspects of RNA metabolism. However, the occurrence of the m 6 A modification in plant circular RNAs has not been reported. A widely used method to identify m 6 A modifications relies on m 6 A‐specific antibodies followed by next‐generation sequencing of precipitated RNAs (MeRIP‐Seq). However, one limitation of MeRIP‐Seq is that it does not provide the precise location of m 6 A at single‐nucleotide resolution. Although more recent sequencing techniques such as Nanopore‐based direct RNA sequencing (DRS) can overcome such limitations, the technology does not allow sequencing of circular RNAs, as these molecules lack a poly(A) tail. Here, we developed a novel method to detect the precise location of m 6 A modifications in circular RNAs using Nanopore DRS. We first enriched our samples for circular RNAs, which we then fragmented and sequenced on the Nanopore platform with a customized protocol. Using this method, we identified 470 unique circular RNAs from DRS reads based on the back‐spliced junction region. Among exonic circular RNAs, about 10% contained m 6 A sites, which mainly occurred around acceptor and donor splice sites. This study demonstrates the utility of our antibody‐independent method in identifying total and methylated circular RNAs using Nanopore DRS. This method has the additional advantage of providing the exact location of m 6 A sites at single‐base resolution in circular RNAs or linear transcripts from non‐coding RNA without poly(A) tails. Abstract : Nanopore‐based direct RNA sequencing cannot sequence circular RNAs, as they lack poly(A) tail. To overcome this limitation, we developed a novel method to detect circular RNAs and m 6 A modification using direct RNA sequencing. This method is also suitable for linear transcripts from non‐coding RNA without poly(A) tails.